Emergency medicine research: 2030 strategic goals. (17th September 2021) - Neumar, Robert W.; Blomkalns, Andra L.; Cairns, Charles B.; D'Onofrio, Gail; Kuppermann, Nathan; Lewis, Roger J.; Newgard, Craig D.; O'Neil, Brian J.; Rathlev, Niels K.; Rothman, Richard E.; Wright, David W.
Abstract: All academic medical specialties have the obligation to continuously create new knowledge that will improve patient care and outcomes. Emergency medicine (EM) is no exception. Since its origins over 50 years ago, EM has struggled to fulfill its research mission. EM ranks last among clinical specialties in the percentage of medical school faculty who are National Institutes of Health (NIH)‐funded principal investigators (PIs; 1.7%) and the percentage of medical school departments with NIH‐funded PIs (33%). Although there has been a steady increase in the number of NIH‐funded projects and total NIH dollars, the slowing growth in the number of NIH‐funded PIs and lack of growth in the number of EM departments with NIH‐funded PIs is cause for concern. In response, the Association of Academic Chairs of Emergency Medicine (AACEM) Research Task Force proposes a set of 2030 strategic goals for the EM research enterprise that are based on sustaining historic growth rates in NIH funding. These goals have been endorsed by the AACEM Executive Committee and the boards of Society for Academic Emergency Medicine (SAEM), American College of Emergency Physicians (ACEP), and American Academy of Emergency Medicine (AAEM). The 2030 strategic goals include 200 NIH‐funded projects led by 150 EM PIs in at least 50 EM departments with over $100M in annual funding resulting in over 3% of EM faculty being NIH‐funded PIs. Achieving these goals will require a targeted series of focused strategies to increase the number of EM faculty who are competitive for NIH funding. This requires a coordinated, intentional effort with investments at the national, departmental, and individual levels. These efforts are ideally led by medical school department chairs, who can create the culture and provide the resources needed to be successful. The specialty of EM has the obligation to improve the health of the public and to fulfill its research mission.